Characterization of humic acids produced from fungal liquefaction of low-grade Thar coal. (August 2021) - Ghani, Madiha Javeed; Akhtar, Kalsoom; Khaliq, Shazia; Akhtar, Nasrin; Ghauri, Muhammad Afzal
Graphical abstract: Highlights: Isolated fungal strains were used to solubilize Thar lignite coal under defined laboratory conditions to extract humic acids. Analyses of extracted products showed increased bioactivity of the products as compared to commercial products. Enzyme activity staining analysis showed the presence of fungal cellulases and xylanases involved in lignite liquefaction. Abstract: Fungal liquefaction of coal is a promising technology to convert low rank coal into value-added products such as humic acids (HAs) that are extensively used as fertilizer. Use of Pakistani Thar lignite for humic acid extraction can promote agriculture industry in Pakistan. In this study, fifty-five fungal strains were isolated from Thar lignite and screened for their lignite solubilization efficiency. Isolates M13 and MI exhibited highest capacity for lignite solubilization and HA was extracted with 67.4 ± 4.3 percent (w/w) yield. Elemental analysis showed increased nitrogen (0.72–1.39 percent) and oxygen (41.7–48 percent), and decreased carbon (51.8–46.1 percent) and sulphur (1.18–0.73 percent) contents in bio-extracted HA (bHA) compared to chemically extracted HA (cHA). UV/Vis spectroscopy showed increased E4/E6 value from 5.6 ± 0.39 (cHA) to 6.28 ± 0.35 (bHA) indicating reduced molecular mass and aromaticity and increased bioactivity of molecule. FTIR analysis also confirmed these results. HPLC analysis of bHA and cHA showed typical choromatogram of humic acids. Enzyme activity staining indicated the presence of fungal cellulase and xylanase on SDS-PAGE gel. The degradation of lignite macromolecules by lignin degrading fungi is a complex process dependent on alkaline substances, chelators, surfactants and extracellular fungal enzymes.